FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI TENAGA KESEHATAN TERHADAP VAKSIN COVID-19 DI PUSKESMAS X TAHUN 2020 - Denny Wulandari; Ade Heryana; Intan Silviana; Erlina Puspita; Rini H; Deasy F (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The importance of vaccination recommendations for health workers (HCWs) to the public is one of the strongest influencers in vaccination decisions. A preliminary study conducted on ten HCWs concluded that they had different perceptions of the COVID-19 vaccine. Different perceptions are influenced by functional function factors (age, gender, education), sociopsychological factors, and structural factors (knowledge, length of work). The aim of the study was to determine the factors related to the perception of HCWs on the COVID-19 vaccine. This type of research is cross sectional with a quantitative approach. The study was conducted in November 2020 - March 2021. The population and sample were 53 HCWs using total sampling method. Data analysis was performed using univariate and bivariate tests using the chi-square statistical test with α = 0.05. The conclusion shows that health workers with negative perceptions 22 people (41.5%), positive perceptions 31% (58.5%), young people 24 people (45.3%), old age 29 people (54.7%), 33 people (62.3%), 20 male (37.7%), 28 people (52.8%) poor knowledge, 25 good (47.2%), 14 new workyears (26.4%) and 39 long years of service (73.6%). The bivariate analysis showed that there was a relationship between health workers' perceptions of the COVID-19 vaccine with age (p value = 0.048, PR = 2.115), gender (p value = 0.029, PR = 2.727), knowledge (p value = 0.030, PR = 2,381). There is no relationship between perceptions of HCWs and years of service (p value = 0.286, PR = 1.592). It is hoped that agencies will provide more socialization and understanding and involve the active role of HCWs so that negative perceptions can be eliminated, considering that vaccine support from HCWs is urgently needed.